Struktur komunitas Tumbuhan Bawah di Zona Pemanfaatan Blok Ireng-Ireng Taman Nasional Bromo Tengger Semeru (TNBTS) - Kurnia, Anisa; Asmuni Hasyim, Muhammad; Nugra Prasetya , Koestriadi (Fakultas Sains dan Teknologi, 2022)
Indonesia is a country that has a very large tropical rain forest. The forest is a unified biological system as part of the earth there is an ordinary organic wealth covered with trees which in cooperation in their nature and current state cannot be separated. Groundcover is a basic vegetation component under forest stands other than tree rejuvenation, which consists of grasses, herbs and shrubs. Bromo Tengger Semeru National Park (TNBTS) is a conservation area with abundant biodiversity, both in terms of flora and fauna. The purpose of this study was to determine the genus of the undergrowth and dominancefound in the Ireng-Ireng Block Utilization Zone, Bromo Tengger Semeru National Park. The research method uses line and transect plots with 4 transects 20 m long, each with 5 plots measuring 1 x 1 m with a distance between plots of 3 m. Result research Found 13 genera as follows Davallia, Strychnos, Homalomena, Nheprolepis, Pheghopteris, Pteris, Ageratina, Sceleria, Molineria, Didymochlaena, Adiantum, Begonia, and Ruellia. The understorey plants that had the highest cover were from the Strychnos genus group with an important value index of 26.87 . Keywords: structure, komposition, Groundcover, ireng ireng block utilization zone Bromo Tengger Semeru National Park.